Association of evening chronotype, sleep quality and cognitive impairment in patients with major depressive disorder - Wang, Li; Huo, Yingchao; Yao, Lihua; Zhang, Nan; Ma, Simeng; Nie, Zhaowen; Wang, Wei; Zhou, Enqi; Xu, Shunsheng; Weng, Shenhong; Xiang, Dan; Hu, Maolin; et al. (Frontiers in Psychiatry, 2024)
ObjectiveThis study aimed to investigate the independent or synergistic effects of evening chronotype and poor sleep quality on cognitive impairment in patients with major depressive disorder (MDD).MethodsA cross-sectional study was conducted on 249 individuals diagnosed with MDD, recruited from the Mental Health Center of Renmin Hospital of Wuhan University. Chronotype preference was assessed using the reduced Horne and Ostberg Morningness - Eveningness Questionnaire (rMEQ), while sleep quality was evaluated using the Pittsburgh Sleep Quality Index (PSQI). Cognitive function was evaluated through the Digit Symbol Substitution Test (DSST), defining impairment as a DSST score ≤ 56 (the lowest quartile of the cohort). Univariate analysis and logistic regression models were employed to explore the factors associated with cognitive impairment, focusing on the potential interactive effects of evening chronotype and poor sleep quality.ResultsOf the 249 subjects recruited, about 41% were classified as evening chronotype. These individuals exhibited poorer sleep quality and more severe depressive symptoms compared to non-evening chronotype (p < 0.01). Univariate analysis revealed that first episode status, Hamilton Depression Rating Scale (HAMD-17) scores, evening chronotype, and poor sleep quality were significantly associated with cognitive impairment (p < 0.05). Multivariate logistic regression analysis further demonstrated that the co-existence of evening chronotype and poor sleep quality significantly increased the likelihood of cognitive impairment (adjusted odds ratio [AdjOR] = 2.65, 95% confidence interval [CI] = 1.09–6.45, p < 0.05).ConclusionOur findings suggest that evening chronotype, poor sleep quality, and their interaction are important contributors to cognitive impairment in patients with MDD, alongside the severity of depression and first episode status. These results emphasize the need for integrated approaches targeting circadian rhythm disruptions and sleep disturbances in the treatment of cognitive dysfunction in MDD.